PELATIHAN PENGGUNAAN MULTIMEDIA INTERAKTIF ARAWA UNTUK GURU SEKOLAH DASAR GUGUS 01 DI KECAMATAN TUBAN - Wendri Wiratsiwi; Lulu Anggi Rhosalia; Mega Puspita Sari (Community Development Journal, 2019)
Training on the use of interactive multimedia ARAWA (Application of Javanese Script) was conducted for primary school teachers in cluster 01 Tuban sub-district, in Tuban district. The training was carried out because in the cluster 01 there was minimal use of learning media to read Javanese on sandhangan scripts which resulted in fourth grade students having difficulties when asked to read Javanese on sandhangan scripts. Even though the Javanese curriculum for fourth grade students should be able to read Javanese script. There are six elementary schools incorporated in this cluster 01, including SDN Kutorejo I, SDN Sendangharjo IV, SDN Baturetno I, SDN Baturetno II, SDN Sukolilo I, and SDN Sukolilo II. The purpose of this training is to introduce and train how to use ARAWA as a medium for learning to read Javanese scripts with a handicap and packaged in learning with innovative learning models for elementary school teachers in 01 cluster 01 Tuban sub-district. The method of implementing this training is carried out with several steps, namely (1) Introducing ARAWA as a medium for learning to read Javanese scripts to primary school teachers in cluster 01 Tuban sub-district, in Tuban district; (2) provide training on how to operate ARAWA for SDN primary school teachers in cluster 01 Tuban sub-district, in Tuban district; (3) Demonstrate how to use ARAWA by applying innovative learning models in Javanese language learning; (4) Accompanying primary school teachers in cluster 01 Tuban sub-district, in Tuban district to facilitate and simplify Javanese language learning for fourth grade by using ARAWA.The existence of this training can improve the ability of teachers to master the material about Arawa and its use, namely using an average value of 92.85. The teacher's response to interactive multimedia is that the five indicators show a positive response.